A partial equilibrium analysis of NAFTA's impact on U.S. bilateral trade - Cephas Naanwaab; Osei-Agyeman Yeboah (International Journal of Economic Sciences and Applied Research, 2014)
This paper examines the effects of the North American Free Trade Agreement on agricultural commodity trade using extensive data. The data cover agricultural exports and imports between the U.S. and NAFTA partners over the extended period of 1989-2010. The commodities covered in the analyses include; corn, soy bean, cotton, wheat, fresh vegetables, poultry, dairy products, and red meats. A partial equilibrium model, in which we derive each trading partner's excess demand and excess supply, is used to study the impact of NAFTA on trade, controlling for other trade-inducing variables such as exchange rates, tariffs, per capita incomes, and relative prices. Regression results show mixed effects of NAFTA on different commodities while graphical and counterfactual analyses indicate strictly positive effects.
Keywords: F13; F14; F15; 330; NAFTA; Agricultural commodity trade; partial equilibrium analysis